1970
DOI: 10.1093/genetics/65.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Mutants of Bacteriophage T4

Abstract: HE apparent mutation rate depends upon a number of contingencies: the Tprimary error rate, the probability o€ repair, error avoidance by the apparatus of DNA replication, and the probability of detection. The probability of detection of those base pair substitutions which produce an amino acid substitution appears to be highly variable, and presumably reflects the sensitivity of polypeptide functions to small variations in primary structure.Fine-scale mapping has often revealed a highly nonrandom distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In a study of 32 diverse higher education institutions in the U.S., GC1 was examined as one of three courses with high DFWI 8 rates (the other two were Calculus 1 and Introductory Accounting). 9 According to this study, the DFWI rate nationally for GC1 is 29.4%. Underneath this, however, in examination of overlapping subsets of race and socioeconomic status, white students experience a DFWI rate of 26.3%, female and male students differ with 25.8 and 33.9% DFWI rates.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…In a study of 32 diverse higher education institutions in the U.S., GC1 was examined as one of three courses with high DFWI 8 rates (the other two were Calculus 1 and Introductory Accounting). 9 According to this study, the DFWI rate nationally for GC1 is 29.4%. Underneath this, however, in examination of overlapping subsets of race and socioeconomic status, white students experience a DFWI rate of 26.3%, female and male students differ with 25.8 and 33.9% DFWI rates.…”
Section: Introductionmentioning
confidence: 74%
“…Addressing inequities in GC1 is further important because DFW rates in GC1 have a strong relationship with retention, which impacts not only students’ access to future opportunities but also the fiscal health of colleges and universities in the U.S. Higher education institutions in the U.S. are increasingly facing challenges due to demographic changes and declining enrollments, the intensification of revenue losses due to inflation and the COVID-19 emergency, the inability to raise tuition due to competition, and increasing costs from measures taken to control inflation . The national study referenced above found that students who took GC1 and continued at the same institution the following year had a DFW rate of 25.9% in GC1, while GC1-takers who were in good overall academic standing and left the institution within one year of taking GC1 had a DFW rate of 49.2% in GC1 . Thus, as there is a relationship between higher DFW rates in GC1 (nearly double) and leaving the institution, actions that higher education institutions can take to improve equity in GC1 are likely to aid in maintaining enrollment, which benefits an institution’s fiscal health, as well as benefiting the institution’s students and their future careers.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Or were the missing sites those at which BPSs simply failed to produce a mutant phenotype? This question was addressed experimentally by Bob Koch (Koch and Drake 1970), a brilliant graduate student who was confined to a wheelchair. Starting with two temperature-sensitive rII mutations that had only a slight mutant phenotype at 30°, Bob treated the corresponding mutants with nitrous acid to produce diverse rII transition mutations.…”
mentioning
confidence: 99%